Whole-Organ Magnetic Resonance Imaging Score (WORMS) of the Knee in Professional Soccer Players - Welsch, Goetz Hannes; Regier, Marc; Frosch, Karl Heinz; Pachowsky, Milena; Henes, Frank Oliver; Adam, Gerhard; Maas, Kai Jonathan; Warncke, Malte Lennart (Cartilage, 2025)
Objective: The goal of our study was to assess the prevalence of osteoarthritis in the knee joint of active male professional soccer players by means of the semi-quantitative Whole-Organ Magnetic Resonance Imaging Score (WORMS). Design: Magnetic resonance imagings (MRIs) of both knees were performed on 85 male professional soccer players during their “medicals” (age = 24 ± 4 years). All baseline data (age, playing position) were obtained. Based on the WORMS, the status of the cartilage and bone in the medial and lateral femoro-tibial joint (MFTJ and LFTJ), as well as the patellofemoral joint was assessed. Menisci and ligaments were evaluated separately. The final score was the sum of all regional scores. Results: The mean WORMS of the 170 knee joints was 13.3 ± 13.5 points (range = 0-111, achievable scores: 0-290). Cartilage changes were the most common pathologies, observed in 141 of the 170 knee joints. Structural cartilage lesions (WORMS ≥ 2) were observed in 54% of the studied knees. Pathologies of the medial meniscus were associated with cartilage damage of the corresponding MFTJ (r = 0.424, P < 0.0001). The same effect was observed for the lateral meniscus and the corresponding LFTJ (r = 0.553, P < 0.0001). However, lateral meniscal lesions could be correlated with more other joint pathologies compared to medial meniscal lesions. Total WORMS correlated significantly with increasing age (r = 0.386, P = 0.001). Conclusion: The provided data show the high incidence of knee joint damage in professional football players. In particular, the lateral meniscus appears to play a critical role.
CRIS-Team Scopus Importer:2025-04-18
Keywords: diagnosis; general; knee joint; magnetic resonance imaging; osteoarthritis; professional soccer; whole-organ magnetic resonance imaging score